2005
DOI: 10.1007/s00198-005-1965-6
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of alendronate and etidronate in the treatment of osteoporosis in men: a prospective observational study

Abstract: The prevalence of osteoporosis in men is higher than previously assumed; consequently, numerous therapies are being investigated to treat these patients. The Canadian Database of Osteoporosis and Osteopenia patients (CANDOO) was analyzed to examine changes in bone mineral density (BMD) in consecutively seen osteoporotic men administered alendronate, etidronate or no bone-active drugs (control) over 1 year. A total of 244 men attending six Canadian osteoporosis clinics were included in the study (42 alendronate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
6
1
Order By: Relevance
“…In one study of 41 men receiving alendronate in a clinical practice setting, any decrease in spine or hip BMD occurred in 10% and 24%, respectively [18], in comparison to 20% and 38% in our study. Veterans’ mean spine D-BMD was 4.2%, similar to a reported one-year increase of 4.2% [19].…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…In one study of 41 men receiving alendronate in a clinical practice setting, any decrease in spine or hip BMD occurred in 10% and 24%, respectively [18], in comparison to 20% and 38% in our study. Veterans’ mean spine D-BMD was 4.2%, similar to a reported one-year increase of 4.2% [19].…”
Section: Discussioncontrasting
confidence: 72%
“…With a mean baseline spine BMD of 1.072g/cm 2 , two-thirds of veterans had ≥3% (0.032g/cm 2 ) improvement between DXAs (mean 1.6 year interval) compared to 87% with ≥3% gain over two years [5]. In veterans, mean hip D-BMD was 0.8% compared to a reported one year increase of 1.6% [18]. With a mean baseline hip BMD of 0.836g/cm 2 , 35% of veterans had ≥3% (0.025g/cm 2 ) improvement between DXAs compared to 63% of men with ≥3% increase in hip BMD over three years [6].…”
Section: Discussionmentioning
confidence: 99%
“…These expert recommendations have been based on several studies primarily established in postmenopausal women [22-27]. Alendronate treatment had been reported in several studies to be effective in improving BMD in men with osteoporosis, similar to its efficacy in women [28-32]. In all the studies, improvement of BMD was observed higher in lumbar spine as compared to femoral neck.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of alendronate in improving BMD was showed in either case of secondary osteoporosis or idiopathic osteoporosis [29, 30]. Compared to etiodronate, alendronate therapy led to significantly greater gains in BMD of lumbar spine [32]. In 1-year observation of alendronate therapy, the mean BMD improvement of lumbar spine was 5.4% - 7.0% and the mean improvement of femoral neck was 2.6% - 4.5% [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Three oral bisphosphonates are used for the prevention or treatment of osteoporosis: etidronate, alendronate, and risedronate. Among these, alendronate and risedronate have been conclusively demonstrated to reduce the number of vertebral and hip fractures in postmenopausal women and to increase bone density in men in the general population [9‐11].…”
Section: Introductionmentioning
confidence: 99%